The Factors Influencing The Education Of Fishing Community: - Jeniba, J.; Uthayakumar, S.S. (South Eastern University of Srilanka, 2019)
Education is inevitable for human resource development. Handling the education effectively could develop a country’s social-economic condition. Thus, this study analyses the factors influencing the education of the students from the fishing community of Pallikuda in the Poonerin division, based on their G.C.E (O/L) results. The objective is to find out whether the factors such as family income, family background, and interest in occupation have influence on the education of the students of this community. The performance in the G.C.E (O/L) examination in the study area is found to be very low. Further, most of the students seem to drop out from the schools after G.C.E (O/L). The data were collected from both primary and secondary resources and the SPSS and MS-Excel software were used to analyze the collected data. The findings of the study show that the family income has less influence on education and there is negative correlation between family income and students’ education. (-21%). However, there is positive correlation (52%) between middle income families and the education. In addition, it is found that the mother’s knowledge has strong influence than father’s knowledge. The number of years studied has (0.572) influence on education. The time spent by the students for education and the time spent by parents for the education of their children are very less. In most of the families, the environment for learning is not found. This study will enable the increase in performance level and solve the issues by setting forth proper solutions.
Keywords: G.C.E O/L; Performance; Education; Income; Family Background; Interest in occupation